Fully integrated voiceband codec in a standard digital CMOS technology. - Pernici, S.
A 2.7-V complete voiceband codec with high-performance speech interfaces is presented. It includes a low-noise microphone preamplifier and loudspeaker/earpiece drivers. In the 4-kHz signal bandwidth, the ADC achieves a dynamic range of 80 dB and a full scale S/(THD + N) ratio of 71 dB, while the DAC performs 84 dB and 75 dB, respectively. These performances have been obtained in a pure digital low-cost CMOS process. The only components used are standard nMOS and pMOS transistors, parasitic vertical PNP bipolar transistors, unsalicided poly resistors, nonlinear poly-nwell capacitors, and a few small linear capacitors made with a sandwich of five metals and poly. The active area is 2.7 mm2 in a 0.35-μm, five metal levels, standard digital CMOS technology. Power dissipation is 12 mW. The cell can be easily migrated in more advanced processes with area reduction. A migration in a 0.18-μm digital CMOS process has been achieved.
Keywords: 0.18 micron; 0.35 micron; 12 mW; 2.7 V; 4 kHz; 71 dB; ADC; CMOS analog integrated circuits; CMOS integrated circuits; DAC; Bipolar transistors; Earpiece drivers; High-performance speech interfaces; Linear capacitors; Loudspeaker drivers; Low power electronics; Low-noise microphone preamplifier; nMOS transistors; Nonlinear poly-nwell capacitors; pMOS transistors; Power dissipation; Signal bandwidth; Unsalicided poly resistors; Voiceband codec